Answer:
Step-by-step explanation:
(a + b + c)³ = a³ + b³ + c³ + 3a²b + 3a²c + 3ab² + 3cb² +3 ac² + 3bc² + 6abc
a = 5a ; b =y ; c = z
(5x + y + z)(5z + y + z )(5z + y +z) = (5x + y +z)³
= (5x)³ + y³ +z³ + 3(5x)²y + 3(5x)²z + 3(5x)*y² + 3*z*y² + 3*5x*z² + 3*y*z² + 6*5x*y*z
= 125x³ + y³ +z³ + 3*25x²y + 3*25x²*z + 15xy² + 3zy² + 15xz² + 3yz² + 35xyz
= 125x³ + y³ + z³ + 75x²y + 75x²z + 15xy² + 3zy² + 15xz² + 3yz² + 35xyz
Answer:
x = -4/9
Step-by-step explanation:
X + B = C
x + (-8/4) = (22/-9)
x = (8/4) - (22/9)
x = 2 - 22/9 = 18/9 - 22/9 = -4/9
Answer:
Step-by-step explanation:
imagine 38 n = lets say b
so b/b/b/b/b
and divide that by 38
Answer:
The answer is C
Step-by-step explanation:
hope this helps